2017
DOI: 10.1212/wnl.0000000000004744
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Training for Upper Extremity in Subacute Stroke (VIRTUES)

Abstract: This study provides Class I evidence that for patients with upper extremity motor impairment after stroke, compared to conventional training, VR training did not lead to significant differences in upper extremity function improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(96 citation statements)
references
References 29 publications
2
88
0
6
Order By: Relevance
“…FMA-UE BBT 2 Kwon et al, 9 , Zheng et al, 27 Rubio et al, 41 Saposnik et al, 26 Kiper et al, 4 Kong et al, 30 Taveggia et al, 24 Brunner et al 28 Quality were considered to increase the confidence in our findings. For the meta-analysis, the standardized mean difference was calculated along with the 95% confidence interval (CI), and the significance level was set at P < 0.05.…”
Section: Ul Motor Functionmentioning
confidence: 86%
See 2 more Smart Citations
“…FMA-UE BBT 2 Kwon et al, 9 , Zheng et al, 27 Rubio et al, 41 Saposnik et al, 26 Kiper et al, 4 Kong et al, 30 Taveggia et al, 24 Brunner et al 28 Quality were considered to increase the confidence in our findings. For the meta-analysis, the standardized mean difference was calculated along with the 95% confidence interval (CI), and the significance level was set at P < 0.05.…”
Section: Ul Motor Functionmentioning
confidence: 86%
“…A meta-analysis was applied to compare changes in the effect size (pre-and post-intervention) between the intervention group (IG) and the control group (CG). Only metaanalyses with greater than or equal to four RCTs included 1 Broeren et al, 5 Housman et al, 39 Piron et al, 40 Kwon et al, 9 Sin et al, 23 Thielbar et al, 29 Kiper et al, 4 Rubio et al, 41 Lee et al, 43 Saposnik et al, 26 Shin et al, 42 Kong et al, 30 Brunner et al 28…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…home) exhibit higher enjoyment and exercise intensity compared to those who exercise alone. Brunner et al (2017) explored the effectiveness of their upper extremity VR rehabilitation system and showed that the improvements were similar to the conventional therapy. They also suggested that the motivating nature of VR could be a supplement to standard rehabilitation.…”
Section: Opportunitiesmentioning
confidence: 99%
“…Rehabilitation therapies offer a chance for an individual to recover and adapt to situation following acute stroke. There has been a large amount of research into methods of rehabilitation management, including task-oriented training [8], impaired limb forced training [9], movement science-based therapy, robotic-assisted movement, virtual reality (VR) training [10], functional electrical stimulation [11], and skill acquisition training paired with impairment mitigation and motivational enhancement and etc.…”
Section: Introductionmentioning
confidence: 99%